Hindu Ritual at the Margins : Innovations, Transformations, Reconsiderations - Clothey, Fred W.; Pintchman, Tracy; Penkower, Linda L. (Columbia : The University of South Carolina Press, 2014)
Hindu Ritual at the Margins explores Hindu forms of ritual activity in a variety of "marginal" contexts. The contributors collectively examine ritual practices in diaspora; across gender, ethnic, social, and political groups; in film, text, and art; in settings where ritual itself or direct discussion of ritual is absent; in contexts that create new opportunities for traditionally marginalized participants or challenge the received tradition; and via theoretical perspectives that have been undervalued in the academy. In the first of three sections, contributors explore the ways in which Hindu ritual performed in Indian contexts intersects with historical, contextual, and social change. They examine the changing significance and understanding of particular deities, the identity and agency of ritual actors, and the instrumentality of ritual in new media. Essays in the second section examine ritual practices outside of India, focusing on evolving ritual claims to authority in mixed cultures (such as Malaysia), the reshaping of gender dynamics of ritual at an American temple, and the democratic reshaping of ritual forms in Canadian Hindu communities. The final section considers the implications for ritual studies of the efficacy of bodily acts divorced from intention, contemporary spiritual practice as opposed to religious-bound ritual, and the notion of dharma. Based on a conference on Hindu ritual held in 2006 at the University of Pittsburgh, Hindu Ritual at the Margins seeks to elucidate the ways ritual actors come to shape ritual practices or conceptions pertaining to ritual and how studying ritual in marginal contexts-at points of dynamic tension-requires scholars to reshape their understanding of ritual activity.
pt. 1 Transformations: history and identity -- The medieval Murukan : the place of a god among his Tamil worshipers / Leslie C. Orr -- A tale of two weddings : gendered performances of Tulsi's Marriage to Krsna / Tracy Pintchman -- The roles of ritual in two "blockbuster" Hindi films / Philip Lutgendorf -- pt. 2 Innovations: globalization and the Hindu diaspora -- The politics of ritual among Murukan's Malaysian devotees / Elizabeth Fuller Collins and K. Ramanathan -- Women, ritual, and the ironies of power at a North American goddess temple / Corinne Dempsey -- Hindu ritual in a Canadian context / Paul Younger -- pt. 3 Reconsiderations: context and theory -- The accidental ritualist / David L. Haberman -- Ritual as dharma : the narrowing and widening of a key term / Alf Hiltebeitel -- From Diaspora to (global) civil society : global gurus and the processes of de-ritualization and de-ethnization in Singapore / Joanne Punzo Waghorne.
Based on presentations at a conference called "Ritualizing in, on, and across the Boundaries of the Indian Subcontinent" in honor of Fred W. Clothey on the occasion of his retirement and held at the University of Pittsburgh in March 2006.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Hinduism -- Social aspects -- Congresses; Hinduism -- Rituals -- Congresses; RELIGION -- Comparative Religion; Hinduism -- Rituals; Hinduism -- Social aspects; RELIGION / Hinduism / General; Electronic books; Conference papers and proceedings